Environmental Factors Associated with Tyfoid Fever in Barru General Hospital - Jama, Rina Silvana (Advances in Healthcare Research, 2023)
Purpose: This study explores the relationship between environmental factors—such as clean water supply, fecal disposal, waste treatment, household waste security, and household drinking water treatment—and the incidence of typhoid fever in Barru District, South Sulawesi. The hypothesis suggests that inadequate environmental sanitation and poor water supply are major contributors to the spread of typhoid fever. Research Design and Methodology: The research utilized a cross-sectional observational design, focusing on 80 Barru Regional General Hospital patients. Respondents were selected through purposive sampling based on specific criteria. Data were gathered through direct observations, structured interviews, and hospital medical records. The Chi-Square test was used to analyze the relationships between the identified variables. Findings and Discussion: The findings indicate a significant relationship between clean water supply and household waste security with typhoid fever incidence. Respondents lacking access to clean water and proper waste management practices showed a higher risk of infection. However, no significant associations were observed between typhoid fever incidence and factors like fecal disposal, waste treatment, or household drinking water treatment. Implications: These results suggest that policy interventions aimed at improving water supply and waste management practices at the community level could effectively reduce the incidence of typhoid fever. Future research should investigate the interaction between these environmental factors and individual behaviors, extending the study to other regions for a more comprehensive understanding.